Corporate accelerator programs : how incumbents' motives and operative support practices impact startup success - Moschner, Sandra-Luisa (Cuvillier Verlag, 2021)
Corporate accelerators are intermediary organizations implemented by incumbent firms to support startups with various resources over a short period of time. Although they are built upon the model of independent accelerators, corporate accelerators do not necessarily aim for financial benefits but for strategic objectives. This thesis examines how corporate accelerators support participating startups and how this support impacts subsequent startups' success based on qualitative and quantitative data. The findings of the study identify corporate accelerator-specific practices that positively influence the success of startups. Further the findings indicate that the extent of support varies, as incumbents initiate the programs as a result of substantive and/or symbolic motives. The findings therefore provide relevant implications for incumbents, corporate accelerator managers and startups.